Hydrogen-based direct reduction of iron oxide at 700°C: Heterogeneity at pellet and microstructure scales - Ma, Yan; Souza Filho, Isnaldi R.; Zhang, Xue; Nandy, Supriya; Barriobero-Vila, Pere; Requena, Guillermo; Vogel, Dirk; Rohwerder, Michael; Ponge, Dirk; Springer, Hauke; Raabe, Dierk (International journal of minerals, metallurgy and materials, 2022)
Steel production causes a third of all industrial CO 2 emissions due to the use of carbon-based substances as reductants for iron ores, making it a key driver of global warming. Therefore, research efforts aim to replace these reductants with sustainably produced hydrogen. Hydrogen-based direct reduction (HyDR) is an attractive processing technology, given that direct reduction (DR) furnaces are routinely operated in the steel industry but with CH 4 or CO as reductants. Hydrogen diffuses considerably faster through shaft-furnace pellet agglomerates than carbon-based reductants. However, the net reduction kinetics in HyDR remains extremely sluggish for high-quantity steel production, and the hydrogen consumption exceeds the stoichiometrically required amount substantially. Thus, the present study focused on the improved understanding of the influence of spatial gradients, morphology, and internal microstructures of ore pellets on reduction efficiency and metallization during HyDR. For this purpose, commercial DR pellets were investigated using synchrotron high-energy X-ray diffraction and electron microscopy in conjunction with electron backscatter diffraction and chemical probing. Revealing the interplay of different phases with internal interfaces, free surfaces, and associated nucleation and growth mechanisms provides a basis for developing tailored ore pellets that are highly suited for a fast and efficient HyDR.